2022
DOI: 10.3390/electronics11081264
|View full text |Cite
|
Sign up to set email alerts
|

Bagged Tree and ResNet-Based Joint End-to-End Fast CTU Partition Decision Algorithm for Video Intra Coding

Abstract: Video coding standards, such as high-efficiency video coding (HEVC), versatile video coding (VVC), and AOMedia video 2 (AV2), achieve an optimal encoding performance by traversing all possible combinations of coding unit (CU) partition and selecting the combination with the minimum coding cost. It is still necessary to further reduce the encoding time of HEVC, because HEVC is one of the most widely used coding standards. In HEVC, the process of searching for the best performance is the source of most of the en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The bagging approach is introduced to address the ensemble bagged tree classifier (EBT). 40 Bagging is the term for bootstrap aggregation, an ensemble learning that generates data using sequential and parallel approaches. 41 In most cases, bagging uses a similar weak classifier and trains them simultaneously.…”
Section: Machine Learning Modelsmentioning
confidence: 99%
“…The bagging approach is introduced to address the ensemble bagged tree classifier (EBT). 40 Bagging is the term for bootstrap aggregation, an ensemble learning that generates data using sequential and parallel approaches. 41 In most cases, bagging uses a similar weak classifier and trains them simultaneously.…”
Section: Machine Learning Modelsmentioning
confidence: 99%
“…Recent studies have demonstrated that CNN-based algorithms [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] outperform traditional learn-based algorithms in terms of the predicting accuracy for the CU partition because they can automatically extract the features and classify them, and accelerate the speed of CU partition while maintaining high coding performance. Liu et al [ 21 ] first applied CNN to HEVC intra-frame CU partition and deployed it on hardware, thereby reducing encoder complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Tahir et al [ 28 ] used a system based on the integration of online and offline random forest classifiers to segment CUs to accommodate the dynamic nature of video content. Li et al [ 29 ] used a new two-stage strategy for the CU fast partition decision. The CTU partition was predicted in the first stage using a bagged tree model.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the coding complexity of the intra VVC encoder, many fast CU decision methods [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] have proposed the acceleration of intra QTMT partition. For example, in [ 19 ], the authors propose a directional gradient-based early termination CU partition method in which four directional gradients (horizontal, vertical, 45, and 135) of CUs are extracted separately to represent the relationship between the optimal CU partition and the texture characteristics of the CU.…”
Section: Introductionmentioning
confidence: 99%
“…In [ 23 ], a fast decision method for QTMT partition with a cascaded decision structure composed of decision trees is proposed. In addition, the authors in [ 25 , 26 , 27 , 28 , 29 ] adopted a deep-learning-based approach for fast QTMT partition decisions. However, these fast CU decision methods for intra QTMT partition cannot be directly used for inter QTMT partition, because the optimal intra CU partition of a CTU is mainly related to the texture characteristics of the CU under the intra coding.…”
Section: Introductionmentioning
confidence: 99%